O Estado de coisas inconstitucional e a atuação do núcleo de situação carcerária da Defensoria Pública do Estado de São Paulo: uma perspectiva redutora de danos - João, Camila Ungar (2022)
The present work aims to critically analyze the phenomenon of the Unconstitutional State of Affairs related to the Brazilian prison system, recognized by the Federal Supreme Court in the context of the provisional measure judgment in ADPF 347. Thus, as a starting point, we approach the illegitimacy of the penal system, with the observation that Criminal Law historically lends itself to the reproduction of social inequalities and racism and that the prison sentence plays a central role in the social control of poverty. In a second moment, we discuss the phenomenon of mass incarceration and its configuration in Brazil. Thus, once the theoretical and factual explanatory framework for such an Unconstitutional State of Affairs has been developed, its practical consequences begin to be demonstrated through data and statistics, which account for the massive and persistent violations of the legal status of prisoners. From this, it is concluded that the Unconstitutional State of Affairs is incurable, as it concerns a prison system that is illegitimate and ungoverned, in the face of massive incarceration of a target audience, so that damage-reducing measures do not lend themselves to making it less unconstitutional, but to narrowing it down, reducing the damage it produces. At this point, we highlight the importance of the adoption, by the Criminal Enforcement Bodies and by the Public Defender Office, given their role in defending the interests of the prison collective of damagereducing practices within the scope of criminal enforcement. Moreover, given the importance of the use of specialized center by the Public Defender Office to help them comply with this ethical mission, it is chosen to exemplify the collective judicial lato sensu action of the Specialized Nucleus of Prison Situation of the Public Defender Office of the State of São Paulo. His territorial action occurs in the State of the Federation, which incarcerates about 1/3 of the entire national prison population. For this purpose, data collection with content analysis is used, based on the agency's Semiannual Activity Reports, in the public domain, within a temporal and thematic perspective, which will indicate that the agency is an important actor in the delegitimization process of punitive power, serving as an instrument for access to justice for the prison population of São Paulo prison system, whose performance has generated favorable results, but still timid, given the need for greater adhering to the other actors of the justice system to an agenda of damage reduction